A conceptual model for a generalized canopy parametrization for atmospheric models. (23rd January 2023) - Cheng, Ge; Schlünzen, K. Heinke
Abstract: The forest canopy and the urban canopy are the two vertically most extended canopies and have a great influence on boundary‐layer processes. Many studies in the past have analyzed and discussed forest canopy effects (FCEs) and urban canopy effects (UCEs) on aerodynamics, thermodynamics, hydrology, and air quality individually. Few studies have compared them. To better understand to what extent FCEs differ from UCEs, this study carries out a qualitative assessment of FCEs and UCEs in comparison with grass‐covered surfaces. In addition, as canopy effects are represented in atmospheric models by employing canopy parametrizations, this study assesses the existing parametrizations with respect to their ability to consider the relevant canopy processes. For parametrizations being globally applicable and for multiple types of forest, urban, and forested urban canopies, it is desirable to treat both forest and urban canopies in models in a unified way. In this context, a conceptual model for a generalized canopy parametrization (GeCap) has been developed based on the assessments of this article. It focuses on the interactions between canopy characteristics, processes, and fluxes as they relate to canopy effects. GeCap can serve as a methodological framework for an integrated analysis of properties and dynamics of canopy systems and for the design of forested urban canopy parametrizations. Abstract : $$ \bullet $$ A conceptual model for a generalized canopy parametrization (GeCap) has been developed based on the assessments of existing parametrizations. $$ \bullet $$ GeCap focuses on the interactions between canopy characteristics, processes, and fluxes as they relate to canopy effects. $$ \bullet $$ GeCap can serve as a methodological framework for an integrated analysis of properties and dynamics of canopy systems and for the design of forested urban canopy parametrizations.